Revisiting the Mechanisms of Immune Evasion Employed by Human Parasites - Chulanetra, Monrat; Chaicumpa, Wanpen (Frontiers in Cellular and Infection Microbiology, 2021)
For the establishment of a successful infection, i.e., long-term parasitism and a complete life cycle, parasites use various diverse mechanisms and factors, which they may be inherently bestowed with, or may acquire from the natural vector biting the host at the infection prelude, or may take over from the infecting host, to outmaneuver, evade, overcome, and/or suppress the host immunity, both innately and adaptively. This narrative review summarizes the up-to-date strategies exploited by a number of representative human parasites (protozoa and helminths) to counteract the target host immune defense. The revisited information should be useful for designing diagnostics and therapeutics as well as vaccines against the respective parasitic infections.